AI-Powered Fraud Detection and Prevention Mechanisms in Online Banking - Sudharshan Putha (Journal of Science & Technology, 2021)
In the digital age, the proliferation of online banking services has necessitated sophisticated fraud detection and prevention mechanisms to safeguard financial transactions from malicious activities. This paper investigates the application of artificial intelligence (AI) technologies in the realm of online banking, with a particular focus on the development and deployment of AI-powered systems for detecting and preventing fraudulent transactions. The primary aim is to elucidate how AI methodologies, such as machine learning (ML) and deep learning (DL), are employed to enhance the accuracy and efficiency of fraud detection processes, emphasizing real-time monitoring and anomaly detection techniques.The paper begins by providing an overview of the current landscape of online banking fraud, outlining prevalent types of fraud and the limitations of traditional detection methods. It then introduces various AI technologies and their relevance to fraud detection. A comprehensive analysis is conducted on how AI algorithms, including supervised and unsupervised learning models, are utilized to identify patterns indicative of fraudulent behavior. Special attention is given to the mechanisms through which AI systems continuously learn from new data, thereby improving their predictive accuracy and reducing false positives.Real-time monitoring is a critical component of effective fraud prevention, and the paper explores how AI-driven solutions facilitate immediate analysis of transactions. The discussion highlights how AI systems leverage vast amounts of transaction data to detect anomalies that deviate from established patterns of normal behavior. The integration of real-time data feeds into AI models allows for the swift identification of potential threats, enabling proactive measures to prevent financial losses.The paper also examines the role of anomaly detection in AI-powered fraud prevention. Anomaly detection algorithms are designed to recognize unusual patterns and deviations in transactional data that may indicate fraudulent activities. The study delves into the various approaches to anomaly detection, including statistical methods, clustering techniques, and neural network-based models. It discusses the advantages and limitations of each approach, emphasizing how combining multiple techniques can enhance overall detection capabilities.Furthermore, the paper addresses the challenges associated with implementing AI-powered fraud detection systems in online banking. These challenges include data privacy concerns, the need for high-quality and representative datasets, and the complexity of balancing detection accuracy with operational efficiency. The discussion includes strategies for overcoming these challenges, such as employing privacy-preserving techniques and optimizing model performance to ensure timely and accurate fraud detection.The paper concludes with a review of case studies that demonstrate the successful application of AI technologies in fraud detection and prevention within online banking environments. These case studies provide insights into practical implementations, highlighting the impact of AI systems on reducing fraudulent activities and improving security measures. The analysis of these case studies offers valuable lessons and best practices for financial institutions looking to adopt AI-driven solutions.This paper provides a thorough exploration of AI-powered fraud detection and prevention mechanisms in online banking. By examining the integration of machine learning and deep learning technologies, real-time monitoring capabilities, and anomaly detection approaches, the paper underscores the significant advancements AI brings to the field of fraud prevention. The insights gained from this study aim to contribute to the ongoing development of more robust and effective fraud detection systems in the ever-evolving landscape of online banking.
Keywords: online banking; financial security